Pengaruh Perendaman Telur Asin Menggunakan Ekstrak Kulit Nanas (Ananas comosus (L.) Merr.) Terhadap Jumlah Bakteri, pH, dan Akseptabilitas - Maulana, Alwi Rizal; Pratama, Andry; Putranto, Wendry Setiyadi (Jurnal Teknologi Hasil Peternakan, 2024)
Eggs are perishable food ingredient. Perishability in eggs can be prevented by salting or making salted eggs. The addition of pineapple peel extract as an antibacterial expected to improve the quality of the eggs. This study aimed to determine the effect of adding pineapple peel extract in the process of making salted egg on the total of bacteria, pH and acceptability. This research was conducted experimentally using a completely randomized design (CRD) with 4 concentration treatments (P0 = 0%, P1 = 1%, P2 = 3% and P3 = 5%) and repetition 5 times. Data on the total of bacteria and pH were analyzed using the test of variance and Duncan's, Post hoc test while the acceptability data was tested using Kruskal-Wallis and continued with the Mann-Whitney post hoc test. The results show that the addition of pineapple peel extract in salted egg process showed a significant effect on the total bacteria, pH and acceptability. The addition of 3% pineapple peel indicate a total bacteria of 6,52x104 CFU/gram, pH 6,87 and still acceptable to the panelists.